2009
DOI: 10.1182/blood-2008-07-166801
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of the CDKN2A gene in childhood acute lymphoblastic leukemia reveals genomic deletion, copy number neutral loss of heterozygosity, and association with specific cytogenetic subgroups

Abstract: Inactivation of the tumor suppressor gene, CDKN2A, can occur by deletion, methylation, or mutation. We assessed the principal mode of inactivation in childhood acute lymphoblastic leukemia (ALL) and frequency in biologically relevant subgroups. Mutation or methylation was rare, whereas genomic deletion occurred in 21% of B-cell precursor ALL and 50% of T-ALL patients. Single nucleotide polymorphism arrays revealed copy number neutral (CNN) loss of heterozygosity (LOH) in 8% of patients. Array-based comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(158 citation statements)
references
References 58 publications
(68 reference statements)
14
141
2
1
Order By: Relevance
“…29,30 Recently, deletions of IKZF1 were shown to be a predictor of poor outcome in high-risk pediatric B-cell progenitor ALL. 31 However, high hyperdiploid ALLs are rarely grouped as high risk.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Recently, deletions of IKZF1 were shown to be a predictor of poor outcome in high-risk pediatric B-cell progenitor ALL. 31 However, high hyperdiploid ALLs are rarely grouped as high risk.…”
Section: Discussionmentioning
confidence: 99%
“…These ''driving'' mutations most likely involve a myriad of different genes giving each cancer case its individual ''face'' but are ultimately converging onto the modification of a finite number of critical pathways. Secondary alterations are well known to occur in hematological malignancies (Bergsagel and Kuehl 2001;Sulong et al 2009). The novel gene fusions presented here might represent secondary lesions that occur at a later time point in prostate oncogenesis.…”
Section: Discovery Of Non-ets Gene Fusions In Prostate Cancermentioning
confidence: 99%
“…This comes in line with four large studies by Woo et al [18] , Mullighan et al [21] , Perez-Vera et al [22] and Sulong et al [10] , they utilized FISH technique with a commonly used commercial probe to study 9p21 deletion in patients with ALL and the deletion frequency ranged from 20-27%. On the other hand this frequency is higher than that recorded by Kuchinskaya et al [12] who identified this deletion in (15.7%) of patients, but is lower than a study done by Schiffman et al [4] who reported this deletion in 29/45 (64.4%) patients and Karkucak et al [19] who detected 9p21 deletion in 8/22 (36%)of patients.…”
Section: Discussionmentioning
confidence: 54%
“…CDKN2A is a tumour suppressor gene that encodes two proteins, and acts through the Rb and mouse double minute 2 (MDM2) pathways. CDKN2B (p15) is a tumour suppressor gene, the action of which through the Rb pathway is complementary to CDKN2A (p16) [10,11] . MTAP is located approximately 100 kb telomeric to CDKN2A and encodes methylthioadenosine phosphorylase, an enzyme involved in purine and methionine metabolism.…”
Section: Introductionmentioning
confidence: 99%